Strengthen the means of implementation and revitalize the global partnership for sustainable development - Nikhil Seth (UN Chronicle, 2015)
The year 2015 will be seminal for the development agenda at the United Nations. Financing sustainable development will be the main subject of an anticipated agreement in Addis Ababa in July 2015. Later, in September of the same year, a global summit will adopt an outcome document containing the post-2015 development agenda, and expectations are high that in December 2015 an ambitious and farreaching agreement will be achieved on climate change in Paris at the twenty-first session of the Conference of the Parties (COP21) to the United Nations Framework Convention on Climate Change (UNFCCC). This array of agreements will frame transformative actions, directions and approaches for people and for our fragile planet.